THE POSSIBILITIES OF USING THE METHODS ANALYSYS OF CONTEXTS AND OVERVIEW PLANS AT FORECASTING OF DEMAND FOR RAILWAY TRANSPORT (Perner's Contacts, 2011)
Presently, the forecasting is an integral part of operational and strategic business plans. Knowing the demand for rail transport is essential for creating a strategy for transport operators and finally also for the infrastructure manager. There are selected those methods of experts methods, which are suitable for prognosis of demand for rail transport. The paper deals with application of methods of analysis of contexts and overview plans for the conditions of railway companies.
Keywords: forecasting; expert methods; qualitative information; ranges of samples; railway transport; transport requirements